Underdeveloping the disadvantaged: the dilemma of globalization on women in a developing country (2019)
Globalization in its meanings and focus is a phenomenon with anticipated promises and possibilities whose impact can be highly felt and appreciated in the face of gender equality. Achieving such may remain an insurmountable brick wall in a developing country like Nigeria. This is especially so when we consider the disadvantage women experience due to the patriarchal nature of the Nigerian system, high level of poverty, increased marginalization and segregation, invisibility and experienced limitations and difficulty in participating and succeeding in power relations, participation in unpaid and less paid jobs (coupled with the devaluation of the Nigerian currency), inability to move and grow in their career pursuit at the same pace with men due to reproductive health issues, socialization of children, women’s “seemingly” unappreciated loss of identity to the men (through marriage) and the general orientation that women are meant to be at the “background”. Conceptualizing globalization from Anderson’s view point and hinged on the theory of feminism, this paper addresses the effect of these disadvantages on women’s lives and opportunities in the Nigerian society at a critical point as this when the country is undergoing economic recession. It concludes that women are more likely to experience underdevelopment despite the possibilities and promises of globalization. It recommends a holistic approach which will involve revisiting some policies, passing some bills, educating, enlightening, re-orientating the necessary stake holders as well as empowering women and re-enforcing gender mainstreaming in all facets of the society in order to reduce the effect of these experiences on their development in the Nigerian society.